Answer:
54
Step-by-step explanation:
since n = 3
= -2n ( 5n+n-8-3n)
= -2 (3) ( 5+(3)-8-3(3) )
= -6 (5+3-8-9)
= -6 (5-5-9)
= -6 (-9)
= 54.
The answer is B, because the numbers in the equation are 2, and -3x. The signs have to stay with the numbers they are with. So if you move the 3 to the front you have to keep the negative with it.
Answer:
2 4/9
Step-by-step explanation:
You need to divide the two fractions.
You need to multiply 11/4 by the reciprocal of 9/8.
11/4 times 8/9
You can simplify first.
11 times 2/9
22/9
Simplify to
2 4/9
It is to be noted that the blanks can only be filled with f(x), range, and domain.
<h3>What are the complete sentences?</h3>
The domain of a function is the set of all input values, or x-values, for which the function is defined.
The range of a function is the set of all output values, or y-values, for which the function is defined.
To write the equation y = ax + b in function notation, substitute f(x) for y.
Learn more about domain at:
brainly.com/question/26098895
#SPJ1
Answer: -920
Step-by-step explanation:
-447 - 473 = -920
In this case, smaller means more negative